»Clearing-house« of ›Trends‹ in Kafka Studies: Deconstruction, Judaism and the Study of Culture at the Intersection of ›Innovativeness‹ and ›Authenticity‹ (KULT_online, 2009)
This anthology means to provide an overview of the most innovative Kafka research published after 1973. The first part introduces three influential perspectives that are grounded in the philosophies of Adorno (Frankfurt School), Deleuze/Guattari (poststructuralism) and Derrida (deconstruction). The second section deals with deconstructivist approaches in a broader sense: those that concentrate on diverse rhetorical mechanisms in Kafka's texts, often subsumed under the terms “logic of signifiers” and “principle of the literality”. The third part contains new, historically precise analyses of Jewish traces in Kafka’s works. The fourth part focuses on cultural and discourse theoretical approaches which emphasise, for example, body and gender concepts. The volume provokes a deeper reflection on the correlation between 'innovativeness' and 'authenticity'.